Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the value of [tex]\( x^3 + \frac{1}{x^3} \)[/tex] given that [tex]\( x + \frac{1}{x} = 7 \)[/tex], we can follow these steps:
1. Express [tex]\( x^2 + \frac{1}{x^2} \)[/tex] in terms of [tex]\( x + \frac{1}{x} \)[/tex]:
We start by squaring both sides of the equation [tex]\( x + \frac{1}{x} = 7 \)[/tex]:
[tex]\[ \left( x + \frac{1}{x} \right)^2 = 7^2 \][/tex]
Expanding the left-hand side, we have:
[tex]\[ x^2 + 2 + \frac{1}{x^2} = 49 \][/tex]
Subtracting 2 from both sides gives:
[tex]\[ x^2 + \frac{1}{x^2} = 49 - 2 = 47 \][/tex]
2. Express [tex]\( x^3 + \frac{1}{x^3} \)[/tex] in terms of [tex]\( x + \frac{1}{x} \)[/tex] and [tex]\( x^2 + \frac{1}{x^2} \)[/tex]:
We use the identity involving cubes:
[tex]\[ (x + \frac{1}{x})(x^2 - 1 + \frac{1}{x^2}) = x^3 + \frac{1}{x^3} + x + \frac{1}{x} \][/tex]
Plugging in the known values:
[tex]\[ x + \frac{1}{x} = 7 \quad \text{and} \quad x^2 + \frac{1}{x^2} = 47 \][/tex]
Therefore:
[tex]\[ x^2 - 1 + \frac{1}{x^2} = 47 - 1 = 46 \][/tex]
3. Substitute the known values into the identity:
We substitute [tex]\( x + \frac{1}{x} = 7 \)[/tex] and [tex]\( x^2 - 1 + \frac{1}{x^2} = 46 \)[/tex] into the identity:
[tex]\[ (x + \frac{1}{x}) \cdot (x^2 - 1 + \frac{1}{x^2}) = x^3 + \frac{1}{x^3} + x + \frac{1}{x} \][/tex]
This simplifies to:
[tex]\[ 7 \cdot 46 = x^3 + \frac{1}{x^3} + 7 \][/tex]
4. Solve for [tex]\( x^3 + \frac{1}{x^3} \)[/tex]:
To isolate [tex]\( x^3 + \frac{1}{x^3} \)[/tex], subtract 7 from both sides:
[tex]\[ x^3 + \frac{1}{x^3} = 7 \cdot 46 - 7 = 322 \][/tex]
So, the value of [tex]\( x^3 + \frac{1}{x^3} \)[/tex] is [tex]\( \boxed{322} \)[/tex].
1. Express [tex]\( x^2 + \frac{1}{x^2} \)[/tex] in terms of [tex]\( x + \frac{1}{x} \)[/tex]:
We start by squaring both sides of the equation [tex]\( x + \frac{1}{x} = 7 \)[/tex]:
[tex]\[ \left( x + \frac{1}{x} \right)^2 = 7^2 \][/tex]
Expanding the left-hand side, we have:
[tex]\[ x^2 + 2 + \frac{1}{x^2} = 49 \][/tex]
Subtracting 2 from both sides gives:
[tex]\[ x^2 + \frac{1}{x^2} = 49 - 2 = 47 \][/tex]
2. Express [tex]\( x^3 + \frac{1}{x^3} \)[/tex] in terms of [tex]\( x + \frac{1}{x} \)[/tex] and [tex]\( x^2 + \frac{1}{x^2} \)[/tex]:
We use the identity involving cubes:
[tex]\[ (x + \frac{1}{x})(x^2 - 1 + \frac{1}{x^2}) = x^3 + \frac{1}{x^3} + x + \frac{1}{x} \][/tex]
Plugging in the known values:
[tex]\[ x + \frac{1}{x} = 7 \quad \text{and} \quad x^2 + \frac{1}{x^2} = 47 \][/tex]
Therefore:
[tex]\[ x^2 - 1 + \frac{1}{x^2} = 47 - 1 = 46 \][/tex]
3. Substitute the known values into the identity:
We substitute [tex]\( x + \frac{1}{x} = 7 \)[/tex] and [tex]\( x^2 - 1 + \frac{1}{x^2} = 46 \)[/tex] into the identity:
[tex]\[ (x + \frac{1}{x}) \cdot (x^2 - 1 + \frac{1}{x^2}) = x^3 + \frac{1}{x^3} + x + \frac{1}{x} \][/tex]
This simplifies to:
[tex]\[ 7 \cdot 46 = x^3 + \frac{1}{x^3} + 7 \][/tex]
4. Solve for [tex]\( x^3 + \frac{1}{x^3} \)[/tex]:
To isolate [tex]\( x^3 + \frac{1}{x^3} \)[/tex], subtract 7 from both sides:
[tex]\[ x^3 + \frac{1}{x^3} = 7 \cdot 46 - 7 = 322 \][/tex]
So, the value of [tex]\( x^3 + \frac{1}{x^3} \)[/tex] is [tex]\( \boxed{322} \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.